The Relationship of Mother's Knowledge and Employment Status with the Provision of PCV Immunization to Babies at the Lembur Health Center, Alor District - Carla Ramiro Guterres; Reni Yuli Astutik; Eri Puji Kumalasar; Putri Eka Sejati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
The leading infectious disease that kills children under five worldwide is still pneumonia. According to the WHO, Indonesia has the eighth-highest pneumonia-related death rate among 15 nations for toddlers and children because of low Pneumococcal Conjugate Vaccine vaccination rates. The study design employs a cross-sectional methodology and correlation analytics. With a population of 300 and a sample of 75, the sampling method used was accidental sampling. The Chi Square test type in SPSS Version 25 was used to examine the results. According to the study's findings, 36% of mothers had high understanding, 64% had poor knowledge, 33.3% were working mothers, 66.7% were not, and 36% had received the PCV vaccine while 64% had not. Maternal knowledge (p value 0.032) and job status with PCV immunization (p value 0.000) were revealed to be related by the Chi Square test. Given that the p value is less than the alpha value (a) = 0.05, H1 is accepted and H0 is rejected, indicating a relationship between the mother's work level and her knowledge and her decision to vaccinate her children against PCV. In addition to knowledge and employment situation, other factors that may impact the decision to vaccinate infants against PCV include age, education, family support, perception, reminders, information the mother has received, distance from home, vaccine composition, and vaccine availability. It is advised that the Community Health Center enhance the way its health education initiatives for infant PCV vaccination are carried out.